Andīshahā-yi falsafī u kalāmi-yi Khwājah Naṣīr al-Dīn Ṭūsī - Farḥāt, Hānī Nuʿmān, (Miras Maktoob, ISBN: 9789004365452., 2019)
Naṣīr al-Dīn Ṭūsī (d. 672/1274) was an influential philosopher, theologian, mathematician and astronomer, besides being the first director of the famous observatory at Marāghah near Tabriz as well as a man of politics. Author of a large number of scholarly works, he is especially famous for such treatises as his Tajrīd al-iʿtiqād on theology, the Zīj-i Īlkhānī on astronomy, the Ḥall mushkilāt al-Ishārāt , his influential commentary on Avicenna's (428/1037) Kitāb al-ishārāt wal-tanbīhāt on philosophy and logic, and his Akhlāq-i Nāṣirī on ethics. In Iran Ṭūsī stands in high regard and studies on him abound. There are a number of monographs on him in Persian, besides proceedings of various Ṭūsī conferences and numerous articles. It is therefore no surprise that the present work by Hānī Nuʿmān Farḥāt, originally published as Al-Khwāja Naṣīr al-Dīn al-Ṭūsī wa-ārāʾuhu al-falsafiyya wal-kalāmiyya (Beirut, 1406/1986), was translated into Persian. Based mostly on Arabic sources, the work focusses mainly on theology and philosophy.